An evaluation of knee osteoarthritis pain in the general community—Asir region, Saudi Arabia - Kandasamy, Geetha; Almaghaslah, Dalia; Almanasef, Mona; Almeleebia, Tahani; Vasudevan, Rajalakshimi; Siddiqua, Ayesha; Shorog, Eman; M. Alshahrani, Asma; Prabahar, Kousalya; Veeramani, Vinoth Prabhu; Amirthalingam, Palanisamy; F. Alqifari, Saleh; et al. (PloS one, 2024)
Knee osteoarthritis (KOA) is one of the most common conditions resulting in disability, particularly in the elderly population. Osteoarthritis (OA) is the most common articular disease and the leading cause of chronic disability in the developed world. This study was carried out to evaluate knee pain in the Asir region of Saudi Arabia. An analytical cross-sectional survey design was adopted in the Asir region from April 2023 to August 2023 to assess the knee pain of the adult population using an anonymous online questionnaire. Of 1234, 332 were men (26.90) and 902 were women (73.09). WOMAC index score category 55.34% (n = 683) of the subjects had a low risk (score <60), 28.68% (n = 354) had a moderate risk (score 60-80), and 15.96% (n = 197) had a high risk (score ≥81) for KOA. According to clinical criteria, 79.33% (n = 979) of the study subjects had OA. Age group, gender 2.17 (1. 67-2.82) [OR 2.17; 95% CI 1.67-2.82), family history of OA [OR 0.47; 95% CI 0.37-0.62], diabetes [OR 2.78; 95% CI 2.17-3.56], hypertension [OR 0.35; 95% CI 0.26-0.45] were significantly associated with the percentage of the WOMAC index score using the Chi-square test analysis (P<0.05). Therefore, the WOMAC index showed higher diagnostic precision with a statistically significant association [OR 9.31 CI 6.90-12.81] with a P< 0.0001. KOA is more common in older, obese people who have reached the age of 50 in the Asir region, and it is more prevalent in women. Alarms the need for appropriate awareness programs for better disease prevention and health outcomes for the benefit of the community through general public health programs.